Managing 'Wayground' as a Multisensory Learning Medium for Students with Autism Spectrum Disorder (ASD) - Betty Margarety; Khairul Anwar; Abdul Rahman; Jumira Warlizasusi (Journal of Educational Management Research, 2026)
This study aims to analyze the management of Wayground implementation as a multisensory learning platform for students with Autism Spectrum Disorder (ASD) at SLB. A qualitative case study design was employed to explore the planning, organization, implementation, and evaluation of Wayground in inclusive learning practices. Data were collected through in-depth interviews, classroom observations, and document analysis involving the principal, classroom teachers, special education teachers, parents, and students selected purposively. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while credibility was ensured through source and technique triangulation, prolonged engagement, and member checking. The findings reveal that Wayground was systematically implemented through four management functions, enabling teachers to integrate visual, auditory, and kinesthetic activities that enhanced students' attention, motivation, engagement, and participation during learning. The implementation was supported by teacher competence, school leadership, technological facilities, and parental involvement, although limited digital devices, unstable internet connectivity, and diverse student characteristics remained challenges. The study implies that effective management of gamified multisensory learning platforms can strengthen adaptive, engaging, and learner-centered educational practices for students with ASD.